(untitled) (Research, Society and Development, 2021)
Considering that cervical cancer is a disease that can affect pregnant women in the same proportion as non-pregnant women, this study aimed to identify the factors that hinder the adherence of pregnant women to the examination during prenatal care, as that this is the most opportune time to do it. An integrative literature review was carried out, using articles available online in the Virtual Health Library (VHL) and in the National Library of Medicne (PubMed) published in the last 5 years, excluding theses, dissertations, duplicate articles and articles that did not fit the theme proposed. Four articles from the aforementioned database were selected to integrate this study. The articles selected for the construction of the work were read in full, in order to identify the factors that hinder adherence. It was possible to identify the low level of knowledge of pregnant women as a barrier, as most believe that the examination during pregnancy can be harmful to the baby or they do not know about what it prevents, believing that it is unnecessary. Other complicating factors were identified, demonstrating that most women are not suitable for the examination during prenatal care. Thus, it emphasizes the need for greater educational actions that help women to clarify the importance of performing the exam during the gestational period, benefiting them with regard to prevention and/or early detection of any abnormality.